Design And Development of Overheat Detector based on Arduino Mega On Four-Wheeled Vehicle Brake System - Aris Budi Sulistyo; Anang Cundoko, Tumiran; Dwifa, Benny; Sasue, Riz Rifai Oktavianus (Journal of Railway Transportation and Technology, 2024)
The aim of this research is to design a motor vehicle braking system trainer, so that it can be used as a test site for overheating detection devices in the brake system. The preparation of the design concept is divided into two designs, namely the designof the braking trainer andalso the design of the software application in the form of asimulation of an overheating detection system. The stages of sensor installation are carried outto the setting and installation of the heat detection sensoris in accordance with the systemplan that has been made, while the placement of the sensor is intended to detect heat from the front and rear braking systems. Programming is also carried out using Arduino software to program the input obtained from the sensor so that it can be displayed on the monitor display. Based on this, a prototype for detecting the brake system for four-wheeled motorized vehicles based on Arduino Mega can be produced. temperature. The four sensors used are able to provide data input and serve as a thermal reference for the conditions of the front and rear brakes, both from brake lining thermals and brake fluid thermals. This prototype also needs further developmentto be applied to real vehicles and to be able to determine the mosteffective location for the sensor so that it can provide the bestinformation to the driver.